2018
DOI: 10.2175/106143017x15054988926433
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment of Mezcal Vinasses by Ozonation and Activated Sludge

Abstract: In Mexico, mezcal production generates huge amounts of vinasses (MV) that cause negative environmental impacts. Thus, MV treatment is necessary before discharge to water bodies. Although there is no information for mezcal vinasses, similar effluents have been treated by biological processes (i.e. anaerobic and aerobic) usually complemented by oxidative chemical pretreatments (ozonation) and physico-chemical methods. In this work MV were first ozonated and followed by batch aerobic biological degradation. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…A low DO content (0.16 to 0.23 mg/L) was due to samples being taken in the underground storage pit and the fact that the vinasse came from an anaerobic process. As is characteristic of this type of effluent, a low pH (3.94) (Cruz-Salomón et al 2017;Robles-González et al 2018;García-Becerra et al 2019), similar values of EC (2.08 to 4.20 mS/cm) to those reported by Robles-González et al (2018), high organic load, however lower than those reported by Robles-González et al (2018) and García-Becerra et al (2019) for mezcal and tequila vinasses, respectively, were observed. There were more than 2 times higher TS than those reported in other studies for mezcal vinasse (García-Becerra et al 2019).…”
Section: Resultssupporting
confidence: 85%
“…A low DO content (0.16 to 0.23 mg/L) was due to samples being taken in the underground storage pit and the fact that the vinasse came from an anaerobic process. As is characteristic of this type of effluent, a low pH (3.94) (Cruz-Salomón et al 2017;Robles-González et al 2018;García-Becerra et al 2019), similar values of EC (2.08 to 4.20 mS/cm) to those reported by Robles-González et al (2018), high organic load, however lower than those reported by Robles-González et al (2018) and García-Becerra et al (2019) for mezcal and tequila vinasses, respectively, were observed. There were more than 2 times higher TS than those reported in other studies for mezcal vinasse (García-Becerra et al 2019).…”
Section: Resultssupporting
confidence: 85%
“…Energy losses in all evaluated growing areas could provide electricity to process at least 80% of the biorefinery's daily milling capacity. However, the gains in soil fertility did not compensate for the losses in environmental quality when in natura vinasse was applied [107].…”
Section: Alternatives For Use Of Sugarcane Vinasse: In Natura and Con...mentioning
confidence: 97%
“…For the treatment of these types of vinasses, as well as similar ones, various biological and physicochemical treatments have been evaluated at the laboratory level: Retes-Pruneda [2] obtained organic matter (OM) removal efficiencies of 92.5% for COD, with a hybrid treatment system consisting of a flocculation stage with alginates and a fungal treatment; Robles-González et al [4] reached removal efficiencies of 85% for OM, 83% for phenols, and 32% for aromatic compounds with a combined treatment of ozonation and activated sludge. Meanwhile, for residues similar to tequila vinasses, anaerobic processes with average OM removal efficiencies that exceed 70% of the influent COD have been reported [5].…”
Section: Introductionmentioning
confidence: 99%